Effect of Dye Extraction From Mangosteen Pericarp With Different Extraction Solvents For Dssc Fabrication - Azira Khairudin; Nurulsyuhada Syahira Shaiful Rahim; Syahida Suhaimi; Mohd Ikmar Nizam Mohamad Isa; Azwani Sofia Ahmad Khiar (Trans Tech Publications Ltd., 2026)
Dye-sensitized solar cell (DSSC) is a well-known solar cell device because it can convert electrical energy from solar energy. In addition, DSSC has many benefits to offer humankind such as low cost in production, flexibility and eco-friendliness. However, the efficiency provided for DSSC operation is still low compared to the efficiency offered by semiconductor materials. Thus, four different solvents are used to extract natural dye from mangosteen pericarp in order to increase the efficiency in DSSC: pure ethanol, ethanol containing 20 % distilled water, ethanol containing 1 % hydrochloric acid (HCl) and ethanol containing 1 % acetic acid. Other than that, the dyes are examined to observe the optical properties by using Fourier transform infrared spectroscopy (FTIR) and ultraviolet-visible spectroscopy (UV-Vis). FTIR analysis resulted in the functional group presence in the dyes while UV-Vis shows that absorption activity exists in the mangosteen pericarp dyes. In addition, the efficiency of mangosteen pericarp dyes with pure ethanol, ethanol containing 20 % distilled water, ethanol containing 1 % hydrochloric acid (HCl) and ethanol containing 1 % acetic acid are calculated which are 0.080 x 10-3 %, 0.554 x 10-3 %, 0.126 x 10-3 % and 0.102 x 10-3 % respectively.